(untitled) (Sebha University Conference Proceedings, 2022)
The research aims to try to reveal the extent of the impact of the political division on the phenomenon of corruption, specifically by monitoring the reality of the performance of the three legislative, executive and judicial authorities, where the descriptive approach and the systems approach were adopted considering that corruption affects and is affected by many surrounding environmental variables, and the case study approach. According to the methodology used in this research, some results have been reached, perhaps the most important of which are: The failure to adhere to the constitutional rules led to the political division, which in turn was one of the important reasons for the spread of the phenomenon of corruption. Issuance of the country’s constitution.